Genome-Wide Investigation of WRKY Transcription Factors Involved in Terminal Drought Stress Response in Common Bean - Wu, Jing; Chen, Jibao; Wang, Lanfen; Wang, Shumin (Frontiers in Plant Science, 2017)
WRKY transcription factor plays a key role in drought stress. However, the characteristics of the WRKY gene family in the common bean (Phaseolus vulgaris L.) are unknown. In this study, we identified 88 complete WRKY proteins from the draft genome sequence of the “G19833” common bean. The predicted genes were non-randomly distributed in all chromosomes. Basic information, amino acid motifs, phylogenetic tree and the expression patterns of PvWRKY genes were analyzed, and the proteins were classified into groups 1, 2 and 3. Group 2 was further divided into five subgroups: 2a, 2b, 2c, 2d and 2e. Finally, we detected 19 WRKY genes that were responsive to drought stress using qRT-PCR; 11 were down-regulated, and 8 were up-regulated under drought stress. This study comprehensively examines WRKY proteins in the common bean, a model food legume, and it provides a foundation for the functional characterization of the WRKY family and opportunities for understanding the mechanisms of drought stress tolerance in this plant.